Structural equation modelling of construction project performance based on coordination factors. Issue 1 (1st January 2020) - Alaloul, Wesam Salah; Liew, Mohd Shahir; Zawawi, Noor Amila Wan; Mohammed, Bashar S; Adamu, Musa; Musharat, Muhammad Ali
Abstract: The construction industry has been dealing with numerous issues in order to achieve the projects' objectives. Hence, caused most projects to suffer low performance, particularly in terms of cost and time overrun and poor quality level. Regarding this matter, the last decade has shown a frequent failure of projects which clearly describes the need for a systematic investigation of the coordination process effects on the performance of the project. The study investigates the impression of coordination factors on projects performance by adopting structural equation modeling (SEM) technique via fit indices and standardised paths. In current research case data were obtained from a questionnaire distributed among owners/developers, contractors, and consultants. A theoretical structural equation model was developed to signify the effect of five main latent variables on project performance. The outcomes showed that projects with high performance have better coordination efficiency. Whereas, planning and scheduling factors (PSF) group is the highest significant group that had a great influence on performance, while records and documentation factors (RDF) group obtained the second important score. Overall, the outcome of this study is expected to contribute to the construction management efforts, particularly in addressing the root causes of poor performance and improving projects success.